Effects of USF1 SNPs and SNP–Environment Interactions on Serum Lipid Profiles and the Risk of Early-Onset Coronary Artery Disease in the Chinese Population - Zheng, Peng-Fei; Chen, Lu-Zhu; Pan, Hong-Wei; Liu, Peng; Zheng, Zhao-Fen (Frontiers in Cardiovascular Medicine, 2022)
Background Upstream transcription factor 1 (USF1) single-nucleotide polymorphisms (SNPs) are significantly associated with serum lipid levels in several different ethnic groups or populations, but their association with lipid levels and the risk of early-onset coronary artery disease (EOCAD) has not been reported in Han populations of southern China. Methods Six USF1 SNPs (rs3737787, rs2774276, rs2516839, rs2516838, rs1556259, and rs2516837) were genotyped by next-generation sequencing (NGS) techniques in 686 control subjects and 728 patients with EOCAD. Results The genotypic and allelic frequencies of the USF1 rs3737787 SNP were significantly different between the control and EOCAD groups. The subgroup analysis identified that the rs3737787T allele was related to a decreased risk of EOCAD, whereas the rs3737787C–rs2774276G–rs2516839A and rs3737787C–rs2774276G–rs2516839G haplotypes were related to an increased risk of EOCAD in men, and the rs3737787C–rs2774276G–rs2516839A and rs3737787T–rs2774276C–rs2516839A haplotypes were correlated with an increased risk of EOCAD in women (p < 0.05–0.01). Male rs3737787T allele carriers had lower low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), and triglyceride (TG) concentrations than the rs3737787T allele non-carriers (p < 0.01). The interactions of rs3737787 with alcohol consumption and rs2516839 with smoking affected serum TC and LDL-C levels in men, whereas the interaction of rs3737787 with alcohol consumption affected serum high-density lipoprotein cholesterol (HDL-C) levels and the rs2516839-smoking interaction affected serum TC levels in women (pI < 0.001). The expression levels of the USF1 mRNA, interleukin 1β (IL-1β), tumor necrosis factor-α (TNF-α), and interleukin 6 (IL-6) were significantly lower in controls than in patients with EOCAD, and rs3737787T allele carriers displayed lower IL-1β, TNF-α, IL-6, and USF1 mRNA expression levels than the rs3737787T allele non-carriers. In addition, IL-1β, TNF-α, and IL-6 expression levels were significantly positively correlated with USF1 mRNA levels (p < 0.01). Conclusion Sex-specific correlations were identified between the USF1 rs3737787T allele with blood lipid levels and the risk of EOCAD. The USF1 rs3737787T allele affects the risk of EOCAD by modulating serum lipid levels and the expression of inflammatory factors, including IL-1β, TNF-α, and IL-6.